Aggregation of Leopardus geoffroyi hybrid embryos with domestic cat tetraploid blastomeres - Duque Rodriguez, Matteo (2021)
Heterospecific embryo transfer of an endangered species has been carried out using recipients from related domestic females. Aggregation of an embryo from an endangered species with a tetraploid embryo from the species to be transferred could improve the development of pregnancy to term. The main objective of the present study was to analyze embryo aggregation in domestic cat model using hybrid embryos. For this purpose, we compared in vitro development of synchronic (Sync) or asynchronic (Async) and asynchronic with a tetraploid (Async4n) aggregation of domestic cat IVF embryos. Furthermore, aggregated blastocyst quality was analyzed by evaluation of the total cell number, cell allocation by mitotrackers staining of embryonic cells, expression of Oct4, Nanog, Sox2, Cdx2 genes, number of OCT4+ nuclei, and presence of DNA fragmentation. Additionally, the developmental rates of Async4n aggregation of domestic cat with Leopardus geoffroyi hybrid (hLg) embryos were evaluated. Async aggregation increased blastocyst cell number and the number of OCT4+ nuclei as compared to non-aggregated diploid (2n) and tetraploid (4n) embryos. Moreover, blastocysts produced by Async4n aggregation showed reduced rates of fragmented DNA. No differences were found in the expression of the pluripotent genes, with exception of the Cdx2 expression, which was higher in 4n and aggregated embryos as compared to the control group. Interestingly, hybrids embryos derived by Async4n aggregation with domestic cat embryos had similar rates of blastocysts development as the control. Altogether, the findings support the use of two-cell-fused embryos to generate tetraploid blastomeres and demonstrate that Async4n aggregation generates good quality embryos.